Unhappiness, health and cognitive ability in old age. - Rabbitt, P; Lunn, M; Ibrahim, S; Cobain, M; McInnes, L (2008)
BACKGROUND: To test whether scores on depression inventories on entry to a longitudinal study predict mental ability over the next 4-16 years. METHOD: Associations between scores on the Beck Depression Inventory and on tests of intelligence, vocabulary and memory were analysed in 5070 volunteers aged 49-93 years after differences in prescribed drug consumption, death and drop-out, sex, socio-economic advantage and recruitment cohort effects had also been considered. RESULTS: On all cognitive tasks Beck scores on entry, even in the range 0-7 indicating differences in above average contentment, affected overall levels of cognitive performance but not rates of age-related cognitive decline suggesting effects of differences in life satisfaction rather than in depression. CONCLUSIONS: A new finding is that, in old age, increments in life satisfaction are associated with better cognitive performance. Implications for interpreting associations between depression inventory scores and cognitive performance in elderly samples are discussed.